THE EFFECTIVENESS OF THE FARMER CARD PROGRAM IN THE DISTRICT OF REMBANG - Puspita, Nadia Ayu; Astuti, Retno Sunu (Journal of Public Policy and Management Review, 2021)
The problem regarding the scarcity of subsidized fertilizers that occurred in many districts of Central Java Province prompted the Governor of Central Java Ganjar Pranowo to create a program to reduce cases of misuse and scarcity of subsidized fertilizers because common problems were still found in the form of scarcity of subsidized fertilizers, delay in distribution of fertilizers, inaccurate targets and prices above which the provisions against the background create the Subsidized Fertilizer Distribution Program. Through the Farmer's Card, which was initiated based on a Ministry Regulation. Rembang Regency is a regency that is experiencing the scarcity problem of subsidized fertilizers so that the Farmers Card is implemented in one of them in Rembang District as an area that uses the most active use and receives the Tani Card. The purpose of this research is to analyze the effectiveness of the Farmer Card Program in the Rembang District and to analyze the factors inhibiting the effectiveness of the Farmer Card Program in the Rembang District and to provide recommendations so that the Farmers Card can be used effectively. This type of research is descriptive using a qualitative approach through the level theory of a program effectiveness by Sutrisno. The results of this study indicate that the understanding of the Farming Card Program can be seen through the initial stages of application until the farmer cards can be run normally, the accuracy of targeting can be seen when the farmer cards are received by farmers who have met complete requirements, the timeliness of the program until the objectives are complete when subsidized fertilizers can be guaranteed The availability and transaction activities of the Subsidized Fertilizer redemption were carried out in an orderly manner while the inhibiting factors were found, among others, despite the system readiness constraints such as EDC machines, different environmental conditions in several other villages and the readiness of implementing agents for farmers who were predominantly elderly farmers to be frequently assisted.